STRATEGIC MANAGEMENT OF THE PUBLIC ART SPACE DESIGN OF PINGCHENG ROAD COMMUNITY - Jiahui, Lu; Saributr, Udomsak (Asia Pacific Journal of Religions and Cultures, 2025)
The strategic management of the public art space design in Pingcheng Road Community, Jiading District, Shanghai, is closely linked to local cultural beliefs and traditions, as it reflects the community’s historical and spiritual values in its aesthetic choices. By incorporating elements of cultural and religious symbolism, the design fosters a sense of collective identity and continuity, enriching the public's connection to their heritage within a modern urban setting. This article explores the strategic management of public art space design in the Pingcheng Road Community of Jiading District, Shanghai, with a focus on integrating cultural beliefs and religious symbolism. It examines how local traditions and spiritual values are embedded in the design process to create spaces that resonate with the community's identity and history. The study highlights the role of public art in fostering social cohesion and enhancing cultural continuity within a rapidly modernizing urban environment. By aligning contemporary design with traditional values, the article demonstrates how strategic management of public spaces can both preserve cultural heritage and meet the aesthetic and functional needs of modern society. This article presented (1) procedures and methods for community space renewal design under the guidance of public arts theory, and (2) strategic management of Pingcheng Road community space design.